Design of a medical equipment management software - Yardımcı, Evrim Ece. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
In this thesis, a medical equipment management system is developed for online access to the medical assets in a healthcare facility to control, plan, schedule and manage the medical equipment preventive maintenance and calibration processes. The system consists of hospital equipment inventory management, personnel imformation in charge of medical equipment, equipment failure and maintenance record registration, preventive maintenance and calibration management, analysis and graphical representations. A password protected, user friendly web interface is provided for easy, universal and secure access to the system. The system is built over a workstation and controlled from an online web site. Microsoft SQL database and .NET platform is used for the preparation of the system. All codes of the system were written with C# programming language.|Keywords: Medical Equipment Management, Preventive Maintenance.
Keywords: Medical instruments and apparatus.; Medical instruments and apparatus -- Maintenance and repair.; Biomedical engineering.